Exploring business and owner traits of small and medium enterprises that exhibit increased revenues in South African townships : the case of selected townships in Strand - Sondlo, Dumisani (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.